635.CRITICAL REACTION FORCES IN THE Z-KINEMATIC LOADERS - Janko Jancevski (MECHANICAL ENGINEERING – SCIENTIFIC JOURNAL, 2021)
The loading processes in industry and mining are the crucial issue in achieving high economic performances. So, there are various kinematic mechanisms and concepts for loading machines. Besides of the loaders with continual work, in this article only one of the most used concepts of loaders, the Z-kinematic loaders are presented. The joints reaction forces during a working process can be extremely high, so it is very important to create simulation computer programs for force and stress calculation in the joints of a loader. Some positions and working loads can produce critical stresses and deformations.